2018
DOI: 10.1016/j.crci.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A novel magnetic biosorbent prepared using an oak shell waste material as an efficient adsorbent for consecutive removal of Pb2+, Ag+, Ba2+, Sr2+, and CrO42− from aqueous solutions

Abstract: In this research, the performance of a new biosorbent prepared using low-cost oak shell waste materials for consecutive removal of particular cations and chromate anions from aqueous solutions was studied. The adsorbent impregnated with Pb 2þ , Ag þ , Ba 2þ , and Sr 2þ was used to remove chromate anions by the formation of an appropriate insoluble precipitate. The biosorbent was characterized by FTIR, XRD, SEM, TG-DTG, and VSM techniques. The adsorption capacities of 133.84, 53.12, 50.12, and 40.39 mg g À1 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This is due to their availability, renewable nature, and low cost [53][54][55]. Some examples of waste biomass sources used in such an application are: rice bran [56], wheat bran [57], sawdust [58], groundnut husk [59], walnut shell [60], switchgrass grass [61], Bacillus laterosporus [62], pine sawdust [63], oak shell [64], and pine cone [65]. The results have shown that these adsorbents have been highly efficient in water treatment.…”
Section: Introduction To Magnetic Nanoparticlesmentioning
confidence: 99%
“…This is due to their availability, renewable nature, and low cost [53][54][55]. Some examples of waste biomass sources used in such an application are: rice bran [56], wheat bran [57], sawdust [58], groundnut husk [59], walnut shell [60], switchgrass grass [61], Bacillus laterosporus [62], pine sawdust [63], oak shell [64], and pine cone [65]. The results have shown that these adsorbents have been highly efficient in water treatment.…”
Section: Introduction To Magnetic Nanoparticlesmentioning
confidence: 99%